Democracy, Constitutionalism, and Politics in Africa: Historical Contexts, Developments, and Dilemmas. - Formella, Collins Nkapnwo (Afrika Tanulmányok / Hungarian Journal of African Studies, 2021)
Collins Nkapnwo Formella Eunice N. Sahle Democracy, Constitutionalism, And Politics In Africa. Historical Contexts, Developments, And Dilemmas. című művét mutatta be.